CLINICAL PROFILE OF NEUROLOGICAL MANIFESTATIONS OF COVID-19 DURING HOSPITAL STAY: A CROSS-SECTIONAL STUDY - VARUN MANJUNATH; SWALEHA NADAF; RAHUL T CHAKOR (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: Since its emergence, coronavirus disease-19 (COVID-19), caused by syndrome coronavirus type 2 (SARS-CoV-2), has shown diverse neurological manifestations, including central nervous system (CNS) complications such as strokes, encephalitis, and delirium. In addition, peripheral nervous system conditions such as Guillain–Barré syndrome, and musculoskeletal issues such as myalgia and rhabdomyolysis are also reported in cases of COVID-19. These are linked to direct viral invasion, hypercoagulability, and immune-mediated injury. Our study during the pandemic systematically evaluated these neurological impacts to understand and address long-term morbidity. Methods: This cross-sectional observational study at a dedicated COVID-19 center in Mumbai evaluated 200 SARS-CoV-2-positive patients for neurological manifestations. Patients were categorized into “Neuro first” and “COVID first” groups based on symptom onset. Comprehensive neurological assessments, laboratory tests, and imaging were conducted. Data were analyzed using SPSS with statistical tests to compare groups, and logistic regression identified factors linked to neurological involvement. Results: Out of 200 COVID-19 patients, neurological manifestations were seen in 47.5%, with significantly higher proportions in severe cases (Stage IIB/III). Common findings included asymptomatic elevated creatine phosphokinase (CPK) (29.4%), headache (18.9%), stroke (15.8%), dysgeusia (14.7%), and anosmia (10.5%). Neurological involvement was 11.6 times higher in severe cases and significantly associated with lower PaO₂ and elevated CPK levels. Severe CNS complications, such as large vessel occlusion strokes and encephalitis, were exclusive to higher disease severity. Mortality was 7.5% overall, with no significant difference between those with and without neurological symptoms. Conclusion: Neurological manifestations such as stroke, headache, and dysgeusia were common in COVID-19 patients. There was a significant correlation between neurological manifestations and disease severity as well as elevated CPK levels.